Climate Change Adaptation: A Study of Digital Financial Inclusion and Consumption Among Rural Residents in China - He, Chunyan; Qiu, Weisong; Yu, Junlin (Frontiers in Environmental Science, 2022)
Climate change impacts agricultural production negatively. Therefore, rural residents experience large income and consumption fluctuations when dealing with climate change risks. However, little is known about whether digital financial inclusion can help rural residents improve their ability to resist climate change. This study uses the Peking University Digital Financial Inclusion Index of China and Chinese Household Financial Survey data, together with historical temperature data from major cities, to study the impact of digital financial inclusion on Chinese rural residents’ consumption in response to climate change. The results suggest that digital financial inclusion significantly promotes rural households’ total consumption and consumption upgrades. Heterogeneity analyses also show that digital financial inclusion predominantly affects low-income households, low assets, and households living in China’s central and western regions. The instrumental variable and the control function methods were used for robustness, and our main conclusions are robust and reliable. Although climate change reduces rural residents’ consumption and increases their risks, digital finance inclusion significantly mitigates this negative effect. Therefore, the government can increase the usage depth of digital financial inclusion in rural areas while promoting the construction of digital financial inclusion facilities, strive for a deeper impact of digital financial inclusion on rural household income and consumption, and further improve their ability to resist climate risks.